Emancipation from transcriptional latency: unphosphorylated STAT5 as guardian of hematopoietic differentiation. (18th February 2016) - Decker, Thomas
Abstract : The canonical paradigm of Jak‐STAT signaling is that members of the signal transducers and activators of transcription (STATs) family of transcription factors are activated by Janus kinase (Jak)‐mediated tyrosine phosphorylation. While the relationship between activation and tyrosine phosphorylation still appears axiomatic, several lines of evidence suggest that unactivated, unphosphorylated isoforms, uSTATs, are nonetheless also engaged in transcriptional regulation. In this issue of The EMBO Journal, Park et al (2015) make a convincing case that nuclear uSTAT5 controls hematopoietic differentiation. Abstract : In canonical Jak–STAT signaling, Jak activates the transcription factor STAT by tyrosine phosphorylation. Now, unphosphorylated STAT5 is shown to directly repress transcription of a different set of target genes, mostly in proximity of CTCF sites, to control hematopoietic differentiation.